2023
DOI: 10.3847/1538-4357/acaefc
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Filament Fibrils and a Network Field

Abstract: Filaments are common structures in the solar atmosphere, and usually interact with their surrounding magnetic fields. However, interactions between filaments and network fields are rare. Here, we report interactions between filament fibrils and a nearby network field in the quiet Sun by employing observations from the New Vacuum Solar Telescope (NVST) and Solar Dynamics Observatory. NVST Hα images show that several filament fibrils separated from the main body of the filament, and moved sideward. While a fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…The filament may be disturbed by its nearby eruptive activities and thus drive material drainage (Dai et al 2021). Song et al (2023) found that the interaction between the filament and its nearby network magnetic fields could also cause material drainage. In prominences, it is possible that the heavy prominence material in the magnetic dips may drag the prominence magnetic fields to sag and drive the magnetic reconnection within or between these sagging magnetic field lines to form vertical downflows that appear as dynamic vertical threads (Chae 2010;Low et al 2012b).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The filament may be disturbed by its nearby eruptive activities and thus drive material drainage (Dai et al 2021). Song et al (2023) found that the interaction between the filament and its nearby network magnetic fields could also cause material drainage. In prominences, it is possible that the heavy prominence material in the magnetic dips may drag the prominence magnetic fields to sag and drive the magnetic reconnection within or between these sagging magnetic field lines to form vertical downflows that appear as dynamic vertical threads (Chae 2010;Low et al 2012b).…”
Section: Conclusion and Discussionmentioning
confidence: 99%